Understanding the Socioeconomic Trajectory of Chavín de Huántar: A New Radiocarbon Sequence and Its Wider Implications. Issue 2 (June 2019) - Burger, Richard L.
Abstract : This article proposes a new 14 C chronology for the three-phase ceramic chronology from the settlement of Chavín de Huántar based on the AMS dating of collagen extracted from faunal remains recovered during my 1975 excavations. The chronometric estimates for the Chavín de Huántar ceramic chronology are as follows: Urabarriu Phase (950–800 cal BC), Chakinani Phase (800–700 cal BC), and Janabarriu Phase (700–400 cal BC). The new measurements confirm the sequence of the ceramic phases and indicate that the site was established around 950 cal BC and was abandoned by 400 cal BC. The results are consistent with the earlier hypothesis that the major developments at Chavín de Huántar largely postdate the Initial Period fluorescence of early coastal civilization during the second millennium BC, but they cast doubt on some current interpretations of the site's founding and cultural apogee. Abstract : Se proporciona una nueva cronología 14 C para las tres fases de la cerámica del asentamiento de Chavín de Huántar. La misma se basa en la datación por AMS del colágeno extraído de los restos de fauna recuperados de las excavaciones realizadas por el autor en 1975. Las estimaciones cronométricas propuestas para la cronología cerámica de Chavín de Huántar son: Fase Urabarriu 950–800 cal aC, Fase Chakinani 800–700 cal aC y Fase Janabarriu 700–400 cal aC. Las nuevas dataciones confirman la secuencia de las fases e indican que el sitio se estableció alrededor de 950 cal aC y fue abandonado alrededor del año 400 cal aC. Los resultados son consistentes con la hipótesis acerca de que el desarrollo principal de Chavín de Huántar es posterior a la fluorescencia del período Inicial de la civilización costera temprana durante el segundo milenio antes de Cristo, pero a la vez generan dudas sobre algunas interpretaciones actuales de la fundación del sitio y su apogeo cultural.